RESTORATIVE JUSTICE DAN PERLINDUNGAN TRAUMA KORBAN KEKERASAN SEKSUAL ANAK DI INDONESIA - Kiki Adha Sirait; Asri Vivi Yanti Sinurat; Syahrani Lailati Br Damanik (Smart Education, 2025)
Abstract: Sexual violence against children constitutes a serious crime that results in multidimensional impacts on victims, including physical, psychological, and social harm. Within the Indonesian criminal justice system, the handling of child sexual violence cases remains predominantly oriented toward a retributive approach that emphasizes the punishment of offenders. Such an approach often fails to fully consider the best interests of the child as a victim, particularly with regard to psychological recovery and the traumatic effects arising from lengthy and confrontational judicial processes. Repeated examinations, the obligation to recount traumatic experiences, and direct or indirect confrontation with perpetrators may exacerbate the victim’s trauma. Restorative justice has emerged as an alternative approach to criminal case resolution by prioritizing victim recovery, offender accountability, and the restoration of social harmony. However, the application of restorative justice in cases of sexual violence against children remains controversial due to the serious nature of the offense and the vulnerable position of child victims. This article aims to analyze the challenges and prospects of implementing restorative justice in the resolution of child sexual violence cases in Indonesia by examining legal protection mechanisms, the principle of the best interests of the child, and the traumatic impacts experienced by victims within the criminal justice process. This study employs a normative juridical research method using statutory and conceptual approaches. The findings indicate that although restorative justice has been accommodated within various legal policies in Indonesia, its implementation in child sexual violence cases continues to face juridical, sociological, and psychological challenges. Nevertheless, restorative justice still holds prospects for limited and selective application, provided that it prioritizes victim protection, ensures strict supervision, and involves professional assistance to safeguard the recovery and well-being of child victims. Keyword: restorative justice, sexual violence against children, legal protection, best interests of the child, psychological trauma. Abstrak: Kekerasan seksual terhadap anak merupakan kejahatan serius yang berdampak luas terhadap kehidupan korban, baik secara fisik, psikologis, maupun sosial. Dalam sistem peradilan pidana Indonesia, penanganan perkara kekerasan seksual terhadap anak masih didominasi oleh pendekatan retributif yang berorientasi pada penghukuman pelaku. Pendekatan tersebut sering kali belum sepenuhnya memperhatikan kepentingan terbaik bagi anak sebagai korban, khususnya terkait pemulihan psikologis dan dampak traumatis yang timbul akibat proses peradilan pidana yang panjang dan konfrontatif. Proses pemeriksaan yang berulang, kewajiban memberikan keterangan di hadapan aparat penegak hukum, serta kemungkinan berhadapan langsung dengan pelaku dapat memperparah trauma yang dialami anak. Restorative justice hadir sebagai pendekatan alternatif dalam penyelesaian perkara pidana dengan menitikberatkan pada pemulihan korban, pertanggungjawaban pelaku, serta pemulihan hubungan sosial. Namun, penerapan restorative justice dalam kasus kekerasan seksual terhadap anak menimbulkan perdebatan karena karakteristik tindak pidana yang serius dan posisi anak sebagai korban yang sangat rentan. Artikel ini bertujuan untuk menganalisis kendala dan prospek penerapan restorative justice dalam penyelesaian kasus kekerasan seksual terhadap anak di Indonesia dengan menelaah aspek perlindungan hukum, prinsip kepentingan terbaik bagi korban, serta dampak traumatis dalam proses peradilan pidana. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa meskipun restorative justice telah diakomodasi dalam berbagai kebijakan hukum, penerapannya dalam kasus kekerasan seksual terhadap anak masih menghadapi kendala yuridis, sosiologis, dan psikologis. Namun demikian, restorative justice tetap memiliki prospek untuk diterapkan secara terbatas dan selektif dengan pengawasan ketat serta pendampingan profesional guna menjamin perlindungan maksimal bagi korban. . Kata kunci: restorative justice, kekerasan seksual terhadap anak, perlindungan hukum, kepentingan terbaik bagi korban, trauma psikologis.